Integrated 3D electrodes based on metal-nitrogen-doped graphitic ordered mesoporous carbon and carbon paper for high-loading lithium-sulfur batteries. (July 2020) - Li, Hao; Liu, Dan; Zhu, Xinxin; Qu, Deyu; Xie, Zhizhong; Li, Junsheng; Tang, Haolin; Zheng, Dong; Qu, Deyang
Abstract: The overall performances of (Li–S) lithium-sulfur batteries are highly dependent on the structure and surface feature of carbon scaffolds as well as the architecture of sulfur cathodes. Herein, a series of semi-graphitic ordered mesoporous carbons with metal/nitrogen doping (Me–N-GOMCs; Me = Fe, Co, Ni, and Cu) are designed as sulfur hosts with abundant porosity and high electrical conductivity. It is revealed that the carbon capability of anchoring polysulfides can be remarkably enhanced through the synergistic effect of Fe and N doping. Moreover, by implanting the Fe–N-GOMC/S composite within the void space of carbon papers (CPs), free-standing integrated sulfur cathodes with the architecture of a continuous conductive 3D network are constructed. The robust ion/electron transport and redox kinetics enable Li–S batteries with excellent sulfur utilization at high loading. The as-acquired CP/Fe–N-GOMC/S electrode with a sulfur loading of 3 mg cm −2 exhibits a high initial capacity of 1473 mA h g −1 and superior cycle stability with a capacity fading as low as 0.075% per cycle over 500 cycles at 0.5C. Even at a sulfur loading up to 6 mg cm −2, the electrode still achieves a steady areal capacity ( 5 mA h cm −2 ) for over 120 cycles at 1C. Graphical abstract: Metal-nitrogen-doped graphitic ordered mesoporous carbons as sulfur hosts are implanted into carbon papers, forming a 3D free-standing integrated sulfur cathode with multifunctionality for Li–S batteries. The cathodes with high sulfur loading demonstrate superior cycle stability while exhibiting high reversible capacities. Image 1 Highlights: A novel type of integrated 3D electrodes with multifunctionality was reported. The cathode with 3 mg cm −2 sulfur loading exhibited 1473 mA h g −1 and 0.075% per cycle fading over 500 cycles at 0.5C. The cathode with 6 mg cm −2 sulfur loading achieved 833 mA h g − 1 over 120 cycles at 1C.